If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18y + 9y = 0 Combine like terms: -18y + 9y = -9y -9y = 0 Solving -9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-9'. y = 0 Simplifying y = 0
| 10-8x=90-36x | | (5v+6)(4-v)=0 | | .25x+.1x=9.8 | | 3[(1)]=x | | 2p+22p^2-p= | | 3[(1)]= | | x^2+31x+5=0 | | Y=-5x+18 | | 24p-28q= | | .25y-10=.1y | | 17+5/15=-4 | | .4x-4=2.8+.2x | | (s/3)+11=16 | | 7+9+x=40 | | 1.12+1.15x=8.62 | | -4t^2+30t-12=0 | | 6-7m-20m^2=0 | | -16+51=-5(x+5) | | 1.12+1.12x=8.62 | | 5=4x-10 | | 8x^2+kx+k=0 | | (4z+1)(8-z)=0 | | 17x-5=11x-35 | | 22+4b=-2(1-6b) | | -0.7x+9.24=-0.5x+8.24 | | -0.7+9.24=-0.5+8.24 | | 3(2x-4)+5=15 | | 9=x/5-1 | | b-7=-4 | | 68=-16t^2-64t-12 | | r-5=20 | | 0.7x-0.5x-6=-4 |